(untitled) (Agrosys: Journal of Agronomy and Sustainable Crop Systems, 2026)
The availability of cassava planting materials through conventional methods remains a constraint to ensuring the availability of high-quality seeds, particularly in dry seasons. One alternative approach is vegetative propagation through grafting, whose success is influenced by the grafting technique and the clones used. This study aimed to evaluate the effects of several cassava clones as scions on grafting success and plant growth, using rubber cassava (Manihot glaziovii) as the rootstock. The experiment was arranged in a randomized complete block design with cassava clones as treatments. Observed variables included grafting success percentage, number of shoots, shoot length, number of leaves, and stem diameter. The results showed that the average success rate of the splice-approach grafting was 83.12%. Clone treatments significantly affected all observed variables. The SH clone exhibited superior performance in most growth parameters, particularly shoot length and stem diameter, while the SL-36 clone showed the highest number of leaves. These findings indicate that clone selection plays an important role in improving grafting success and supporting the production of high-quality cassava planting materials.